Development of a Training Curriculum Structure to Improve ICT Competencies of Teachers in Primary Schools - Syahid, Aah Ahmad; Isrokatun, I; Nugraha, Dadan (Universitas Pendidikan Indonesia, 2019)
Possessing ICT skills for learning was a necessity for primary schools teachers in accordance with the requirements of current development and Education 4.0. This multi-year research had entered its third year in which it sought to discover information about the types of ICT training materials that were appropriate for the needs of teachers in primary schools and development of effectiveness of an ICT training curriculum structure. This research employed a descriptive survey design. The sample included 30 teachers in primary schools from 12 regions with different school characters in Sumedang Regency, West Java. The findings of this research showed an overview of a gap between teachers who had capabilities in utilizing ICT and teachers who needed to develop their capabilities in utilizing ICT through a practice. In attempting to mediate this gap, this research designed an ICT training curriculum structure that was appropriate for the needs of teachers in primary schools.